(untitled) (African Journal of Biomedical Research, 2020)
Clarias gariepinus is an important species of fish that is a major component and source of animal proteins in most diets of the people of Zaria in particular, and Nigeria in general. This work assessed the concentrations of some heavy metals; lead (Pb), manganese (Mn) and cobalt (Co) in different parts of Clarias gariepinus from rivers Galma and Kubani and fish farms in Zaria, using Atomic Absorption Spectrophotometer, after wet digestion. The concentrations of the metals differed significantly across the different parts of the fish, with Pb levels being the most worrisome. Across the different sources, the results showed that fish caught from the wild (river Galma and river Kubani) have their metal concentrations comparatively higher than those gotten from fish farm. Generally, the concentrations of the metals in the different parts of the fish, across the sources were significantly higher (P<0.05) compared to the FAO/WHO and EU permissible limits of these metals in fish. This shows a possible high risk of heavy metal toxicity consequent upon the consumption of this fish from these sources